What Drives Systemic Mental Health Advocates? Goals, Strategies, and Values of Australian Consumer and Carer Advocacy Organizations. (11th November 2015) - Gee, Alison; McGarty, Craig; Banfield, Michelle
The consumer participation movement has growing international recognition in policy and research. Focusing on the collective context, this research systematically examines how two advocacy organizations in the Australian mental health sector are organized and motivated to advance the cause. Qualitative studies analyzed 17 strategic communication documents and nine interviews with members and staff to identify major themes relating to goals, activities, and values driving advocates and their organizations. Five major focus issues were identified: building consumer and carer participation, voice and recognition for consumers and carers, influencing and improving mental health systems, effective collaboration and partnerships, and building organizational strength. Findings demonstrate what drives consumer and carer advocates and their organizations to contribute to an organized, strong, and unified movement. While they focus on cementing genuine and effective consumer participation in health service and policy, they highly value partnerships based on mutual respect to improve mental health systems and outcomes.